NRF2 activation by myeloid cell–derived oxidative stress induces SNAI-driven features of EMT in breast cancer - Mustafa Kaya; Olivia Johnsson; Nuttida Issdisai; Sanchari Paul; Clotilde Wiel; Anushka Dongre; Kristoffer Hellstrand; Anna Martner (Proceedings of the National Academy of Sciences, 2026)
Metastasis is facilitated by epithelial-to-mesenchymal transition (EMT), a process in which epithelial cancer cells, including breast cancer cells, acquire mesenchymal-like phenotypes. Production of reactive oxygen species (ROS) by NADPH oxidase 2 (NOX2) is a principal inflammatory and antimicrobial feature of myeloid cells. Inflammation has been linked to EMT, but the role of ROS released from tumor-infiltrating myeloid cells in EMT is unknown. In coculture experiments with human or murine myeloid cells and breast cancer cells, we observed that NOX2-derived ROS induced EMT-like changes in MCF-7, T-47D, 4T1, and EO771 cells via activation of SNAI transcription factors, mediated by the ROS-sensitive transcription factor NRF2. Intratumoral administration of the NOX2/ROS-activating peptide WKYMVm to mice carrying orthotopically implanted 4T1 or EO771 tumors increased primary tumor growth, augmented tumor cell expression of EMT markers and aggravated distant metastasis. Effects of ROS released from myeloid cells were mimicked by exogenous hydrogen peroxide (H 2 O 2 ) and reversed by a ROS scavenger or a NOX2 inhibitor. In accordance, myeloid cells from Nox2 -deficient mice were less prone to induce EMT in breast cancer cells in vitro or in vivo. Analysis of publicly available human breast cancer datasets showed correlations between NOX2 and EMT-related gene expression within the tumor microenvironment. Additionally, high expression of NOX2 subunit genes and SNAI1 associated with reduced metastasis-free survival. These findings imply that myeloid cell–derived ROS initiate partial EMT in breast cancer cells to promote dissemination and that strategies to target myeloid cell–derived ROS may be explored to limit metastasis.